2013
DOI: 10.9728/dcs.2013.14.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Influence of LTE Characteristic and Personal Innovativeness on LTE Smart Phone Acceptance

Abstract: This study is to derive the factors that influence the acceptance of LTE smart phones. Using an extended technology acceptance model to look at the factors affecting the acceptance LTE smart phone. Variables and the LTE features on the personal characteristics variables were chosen based on the study. This study was done through a survey. Surveyed LTE smart phone's primary audience, taking into account the age of 20 were analyzed mainly. LTE smart phone's acceptance factors affecting individual innovation, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Research explaining the factors affecting people's behavior to use an information system was the mainstream in the IS (information System) literature for several decades [15][16][17][18][19]. Of diverse models studying people's use of information systems and information Technology, TAM has been used repeatedly and is widely known [3].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
See 4 more Smart Citations
“…Research explaining the factors affecting people's behavior to use an information system was the mainstream in the IS (information System) literature for several decades [15][16][17][18][19]. Of diverse models studying people's use of information systems and information Technology, TAM has been used repeatedly and is widely known [3].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Gu et al [15] suggested fun, speed, security, and price as external variables influencing perceived usefulness in the study that analyzed acceptance intention of the LTE smartphone. In LTE service, it's the communication fee that people are concerned most about [37].…”
Section: The Hypothesis and Proposed Modelmentioning
confidence: 99%
See 3 more Smart Citations